ANALISIS KINERJA KARYAWAN STUDI KASUS PADA ICHIBAN SUSHI MAGELANG (MOTIVASI, 2022)
Purpose. The purpose of this study was to determine and analyze how the performance appraisal of employees at Ichiban Sushi Magelang, with a qualitative approach, and using instruments through interviews, observation and document review.Design / Methodology. with a qualitative approach, and using instruments through interviews, observation and document review. While the data collection techniques through interviews, observation and document review. Data processing techniques using descriptive analysis.Findings. The results of the study that employees in completing work on average have worked according to the target and have been able to improve the performance of Ichiban Sushi Magelang employees. Judging from the aspect of work quality, the error rate is still low in completing the work and besides that every employee in completing the work is in accordance with what is determined by the company. Viewed from the aspect of timeliness, employees have the ability to complete every job properly and on time. Viewed from the aspect of attendance, that the level of employee attendance is relatively high because employees are on time when they come to work. Meanwhile, in terms of the ability to cooperate. Where in this study it was found that employees in doing work always cooperate with other co-workers well and besides that there is also a good relationship between superiors and subordinates.